Effect of Haptic Training During Manual Wheelchair Propulsion on Shoulder Joint Reaction Moments - Aissaoui, Rachid; Gagnon, Dany (Frontiers in Rehabilitation Sciences, 2022)
Background: Manual wheelchair propulsion remains a very ineffective means of locomotion in terms of energy cost and mechanical efficiency as more than half of the forces applied to the pushrim does not contribute to move the wheelchair forward. Manual wheelchair propulsion training using haptic biofeedback has shown an increase in mechanical efficiency at the handrim level. However, no information is available about the impact of this training on the load at the shoulders. We hypothesized that increasing propulsion mechanical efficiency by 10% during propulsion would not yield clinically significant augmentation of the load sustained at the shoulders. Methods: Eighteen long-term manual wheelchair users with a spinal cord injury propelled a manual wheelchair over a wheelchair simulator offering haptic biofeedback. Participants were asked to propel without haptic feedback and thereafter, they were subjected to five training blocks of 3 minutes in a random order with haptic biofeedback targeting a 10% increase in force effectiveness. Pushrim kinetics, shoulder joint moments and forces during the propulsive cycle of wheelchair propulsion were assessed for each conditions. Results: Statistically significant increases in the resultant force, the tangential force component and the mechanical effective force between the pre-training and training blocks were found. Statistically significant increases were found for the shoulder joint moments and forces but of relatively small amplitudes. Conclusions: Increases in shoulder loads were found for the corresponding training blocks but were of low amplitude and of little clinical incidence at the shoulder. The use of a HB simulator is a safe approach to increase mechanical effectiveness during manual wheelchair propulsion since very limited impact was found at the shoulders.